Does marital status impact postoperative survival in patients with less differentiated hepatocellular carcinoma? A population‐based study - Bing Yan; Dou‐Sheng Bai; Jian‐Jun Qian; Chi Zhang; Sheng‐Jie Jin; Guo‐Qing Jiang (Cancer Medicine, 2019)
Abstract Background Marital status has long been widely recognized as a determinant of cancer survival. However, only few analytical studies have been conducted on this issue considering heterogeneous factors. The aim of this study was to assess the effects of marital status on postoperative survival of patients with less differentiated (poor/anaplastic) hepatocellular carcinoma (HCC). Methods We retrospectively analyzed 1581 postoperative patients diagnosed with poor/anaplastic HCC from the Surveillance, Epidemiology, and End Results database between 2004 and 2015. Patients were classified into married, never married, divorced/separated and widowed groups. Kaplan‐Meier analysis and multivariate Cox regression analysis were used to analyze the effects of marital status on HCC cause‐specific survival (HCSS). Results Compared with married patients, there were no significant differences in HCSS for unmarried, never married, divorced/separated and widowed patients both in univariate (5‐year HCSS: 36.0% vs 36.3%, 36.0% vs 32.4%, 36.0% vs 40.2%, 36.0% vs 36.3%, respectively, all P > .05) and multivariate analysis (all P > .05). Furthermore, in stratified analyses according to sex, age, and tumor size, compared with married patients, there were also no significant differences for never married, divorced/separated, and widowed patients both in univariate (all P > .05) and multivariate analysis (all P > .05). Conclusions For patients with poor/anaplastic differentiated HCC treated with surgical resection, marital status has no prognostic role in survival.